ASSESSMENT OF COMPLETE BLOOD COUNT IN PATIENTS WITH CORONARY ARTERY DISEASE (Iraqi Journal of Medical Sciences, 2016)
Background:Several studies have demonstrated the role of hematological parameters like hemoglobin (Hb), white blood cells (WBC) count and platelet count in the assessment of patients with coronary artery disease; some studies suggest an additional role of platelet indices in the prognosis of patients with coronary artery disease.Objective:To assess complete blood count and platelet indices in patients with coronary artery disease.Methods: Blood sample of 42 newly diagnosed ischemic heart disease patients including 20 patients with myocardial infarction (MI) and 22 patients with unstable angina were studied. The control group included 15 individuals with no history of heart disease and a normal electrocardiogram. Clinical and laboratory information regarding age, sex, packed cell volume, WBC count, platelets count, platelet distribution width and platelet volume were obtained.Results:The frequency of diabetes and smoking was higher in patients with coronary heart disease in comparison to the control group (P < 0.05), while the frequency of hypertension was not significntly different. Significant difference in WBC count and Hb level of patients with coronary heart disease (P < 0.05), while no significant difference in the platelet count, platelet distribution width and mean platelet volume was found. In patients with unstable angina there was a significant difference in the Hb level (P < 0.05) while no significant difference in WBC count, platelet count, platelet distribution width and mean platelet volume was observed. In patients with myocardial infarction, there was a significant difference in the Hb level and the WBC count (P < 0.05), whereas no significant difference in platelet count, platelet distribution width and mean platelet volume was found.Conclusion:Hemoglobin level was significantly lower in patients with coronary artery disease while the mean level of WBC count was significantly higher than that of the control group. There was no significant difference in platelet count and platelet indices between those two groups. In patients with unstable angina the WBC count was not statistically different from that of the control group.Key words:Coronary artery disease, Hb, WBC, PDW, MPV.
Keywords: Coronary artery disease; Hb; WBC; PDW; MPV